THE EPISTEMOLOGY OF THE HUDAN GUIDANCE OF THE QURAN AS A FRAMEWORK FOR ESTABLISHING THE VALIDITY OF THE MAQASID OF THE QURAN - Siti Hajar (Al-Mubin, 2026)
This article examines the epistemology of the Quranic hudan as a conceptual framework in confirming the validity of contemporary interpretations of the maqasid of the Quran Hudan is understood not merely as a normative guide but as an epistemic system that guides the human reasoning process in understanding the objectives of revelation This study aims to show that the formulation of the maqasid of the Quran must be rooted in a divine orientation so as not to be trapped in rational relativism and pragmatic interests By using a qualitative approach based on literature studies and conceptual analysis this article asserts that the epistemology of hudan functions as a normative methodological and evaluative foundation in the interpretation of maqasid The results of the study indicate that hudan is able to maintain a balance between loyalty to revelation and responsiveness to social reality so that the maqasid of the Quran remains relevant valid and has theological legitimacy in responding to the challenges of the contemporary era.